Recontextualizing the City of Medina as the Epicenter of Islamic Education During the Time of the Prophet Muhammad, Peace Be Upon Him - Kurnia, Nia; Ningsih, Fitria; Roza, Ellya (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This article discusses the role of Medina as a center of Islamic scholarship and education during the time of the Prophet Muhammad (peace be upon him). After the migration from Mecca, the Prophet Muhammad made Medina not only the center of government, but also the center of civilization and the development of Islamic knowledge. Educational activities during that period took place through several institutions such as the Prophet's Mosque, Suffah, and Kuttāb, which served as means of fostering faith, worship, morals, and literacy among the Muslim community. This study examines in depth the Islamic education system in Medina during the time of the Prophet Muhammad (peace be upon him), which includes educational institutions, the role of the companions as teachers, and the learning methods applied by the Prophet Muhammad (peace be upon him) as the main educator with the support of his companions who also acted as teachers. The educational methods applied included exemplary behavior (uswah ḥasanah), dialogue, habituation, memorization of the Qur'an, and the dispatch of teachers to various regions. This research uses a literature study method with a descriptive qualitative approach to examine primary and secondary sources regarding the Islamic education system during the time of the Prophet Muhammad (peace be upon him), using in-depth analysis and a literature review. The results of the study show that education in Medina is integral, inclusive, and oriented towards the formation of a well-rounded personality, covering cognitive, spiritual, social, and moral aspects. The education system established by the Prophet Muhammad in Medina became the main foundation for the birth of a sustainable Islamic scholarly tradition that remains relevant as a model for Islamic education throughout the ages, integrating structured institutions, competent teaching staff, and effective learning methods.